The Distribution of Bathyarchaeota in Surface Sediments of the Pearl River Estuary Along Salinity Gradient - Zou, Dayu; Pan, Jie; Liu, Zongbao; Zhang, Chuanlun; Liu, Hongbin; Li, Meng (Frontiers in Microbiology, 2020)
Bathyarchaeota, a recently proposed archaeal phylum, is globally distributed and highly abundant in anoxic sediments. Metabolic pathways of the Bathyarchaeota members are diverse and, hence, this phylum has been proposed to play an important role in global biogeochemical cycles. Bathyarchaeota members are distributed in the estuarine environments. However, limited information is available about their detailed community structure, abundance, and functions in the Pearl River estuary (PRE). In the current study, we performed a comprehensive investigation of the archaeal community in the PRE surface sediments along a salinity gradient, with a focus on Bathyarchaeota. Bathyarchaeota was the dominant archaeal phylum, with the abundance of the bathyarchaeotal 16S rRNA gene ranging from 1.43×108 to 1.22×109 copies/g sediment dry weight (d.w.), and Bathy-8 was the dominant subgroup. Thaumarchaeota, Lokiarchaeota, and Euryarchaeota, including Thermoprofundales (MBG-D archaea), were the other major archaeal groups in the PRE. The differences of community distributions in the high- and low-salinity sediments were hence investigated. Statistical analysis revealed that besides salinity, ammonium and total organic carbon (TOC) were the most important environmental factors influencing the archaea community structure, including that of Bathyarchaeota, in the PRE. The archaeal network indicated the cooccurrence among Bathyarchaeota, Lokiarchaeota, and Euryarchaeota, while Bathy-6 presented unique correlations compared with other bathyarchaeotal subgroups. These observations indicate that Bathyarchaeota may play a role in ecosystem function through microbe-microbe interactions, revealing a possible different lifestyle for Bathy-6 in eutrophic estuarine sediments.